PRODUCTION OF BIODIESEL FROM CORN AND COCONUT OIL WITH LOCALLY JEMBER INDONESIA VEGETABLE OIL: An optimization of biodiesel parameters - Azamataufiq Budiprasojo; Alex T. Zain (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
In this study, experimental trials will be carried out to find out the optimal recipe for processing corn oil and biodiesel oil produced by UMKM in Jember Regency (Indonesia) into biodiesel known as biosolar. Experimental conditions will be optimized to obtain partial transesterification of coconut oil and corn oil using a variety of common methoxide for the production of biosolar. Biosolar production using conventional methods has not yet produced fuel that meets modern engine standards, further research is needed to overcome this problem, including by making an advanced processing method. The following experimental parameters will be varied : liquid temperature (40-60ºC), processing time (1800 to 3600 sec.), catalyst (0.5-1,25 % of total weight.), and proportional of methanol oil mix ratio (m/o) (1:3-1:6). The maximum value parameter of biodiesel reaching 98.12% was produced by methoxide from KOH at 60 minutes of process, in 60 oC temperature and an oil – methanol mix ratio of 1:0.25. The optimal conditions for biosolar production also with biosolar fuel properties varied catalysts were tested with the standard methods of 14214EN and ASTMD6751. The results showed that optimum catalysts for biosolar production using coconut oil and corn oil are 0.8 % of total weight of either KOH and NaOH catalyst.